Characteristics of SH waves in multilayered piezoelectric semiconductor plates considering interfacial imperfection - Luo, Y.H.; Zhang, X.M.; Gao, A.R. (Archives of Mechanics, 2025)
The dispersion and attenuation characteristics of SH waves in piezoelectric semiconductor multilayered plates with imperfect interfaces are investigated using the improved Legendre orthogonal polynomial method. The field quantities of each layer are expanded into individual Legendre polynomials. By incorporating the interface conditions, the imperfect interface model is integrated into the Legendre polynomials associated with the imperfect interface layer. This method ultimately converts the complex wave partial differential equations into a generalized eigenvalue problem, thereby eliminating the redundant integration operations typical of traditional polynomial methods and allowing for the derivation of complete solutions throughout the entire wave frequency domain. The solutions are then plotted in three-dimensional frequency-complex wavenumber space, thus gaining much deeper insight into the nature of modes. The study encompasses cases ranging from a single-layer ZnO plate, which serves to validate the method, to bilayered and sandwiched piezoelectric semi-conductor plates with imperfect interfaces. The effects of steady-state carrier concentration, imperfect interface coefficients, and stacking sequences on the phase velocity, dispersion, and attenuation curves of SH waves are illustrated. The findings can offer a theoretical foundation for controlling the wave characteristics of piezoelectric semiconductors and for the design of acoustic devices.